If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 56 + -2x = 7x + 21 Reorder the terms: 56 + -2x = 21 + 7x Solving 56 + -2x = 21 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 56 + -2x + -7x = 21 + 7x + -7x Combine like terms: -2x + -7x = -9x 56 + -9x = 21 + 7x + -7x Combine like terms: 7x + -7x = 0 56 + -9x = 21 + 0 56 + -9x = 21 Add '-56' to each side of the equation. 56 + -56 + -9x = 21 + -56 Combine like terms: 56 + -56 = 0 0 + -9x = 21 + -56 -9x = 21 + -56 Combine like terms: 21 + -56 = -35 -9x = -35 Divide each side by '-9'. x = 3.888888889 Simplifying x = 3.888888889
| 3/4k-5=-1+1/4 | | 6*x/2=4*x/2 | | 2x-4+3(x-2)=0 | | (9y^2+5y+2)-(2y^2-5y+9)= | | 2/3(a-2)+6=18 | | C/5=4 | | x^2+6x-97=0 | | 6(x+5)=-4x+6+2x | | 4.5/18 | | 3x-5(x+3)=2x+15 | | 5(3x-5)-7(2x+5)+9(3x-2)= | | x+5+x-2=54:15 | | x+5=54 | | (6y^2-5y+6)-(9y^2-5y+7)= | | -1.4-(0.2x+3)=0.8x-1.2 | | 4x^2+18x-1882=0 | | x+5+x-2=54-15 | | -5=x+10 | | x+5+x-2=54 | | 6(5x+4)+2(3x-7)-5(7x-4)= | | 5(2t+5)= | | x+(x*12.36/100)=450648.16 | | 3x^2+24x=0forx | | 3/4x+5/4-1/4 | | 21x+77-18x+54= | | 16^2/3 | | ln(3x^2)=8 | | N*18=126 | | -5+8-4(2y+1)= | | 18x+36+12x-21= | | 9/4x=6/2 | | 2x+15=5x+14 |